A customizable method for handling line joins for map representations based on shader language. Issue 3 (2nd July 2016) - Zheng, Peibei; Peng, Guoqiang; Yue, Songshan; Lu, Guonian
ABSTRACT: The rendering of line joins is important for representing linearly changing information and for allowing map readers to develop a more comprehensive understanding of the real world from maps. Although a range of software-based and graphic processing unit (GPU)-accelerated rendering methods have been developed to render wide lines, linear map symbols are much more complicated compared to commonly used line types in drawing geometric lines, and the rendering of lines joins should consider a filling process that is continuous, rational and efficient. This paper proposes an improved method to generate and adjust the U – V parameters (which are used to control the rendering process of linear map elements within the GPU shader language) of the vertices in line joins to provide a customizable approach for map designers to implement different drawing effects of line joins for drawing different line elements. Based on the customizability, the continual and rational rendering of line joins are studied. Two experiments are conducted to demonstrate the method's feasibility and efficiency; the results demonstrate that line joins can be effectively and rationally drawn with a variety of linear map symbols. The efficiency of rendering linear map elements is also improved with this method.